Structural Study of the Short Story Title Eyang by Putu Wijaya - Nailah Faizah S Rambe, Putri Alicya Zafira, Safinatul Hasanah Harahap (Education Achievement: Journal of Science and Research, 2023)
This article aims to determine the structural structure of the short story Eyang Karya Putu Wijaya. The approach used is qualitative by reading and observing Eyang's short stories. The results of the research provide an illustration that the short story Eyang was formed coherently by Putu Wijaya, so that it has coherence and relationships between elements and other elements. The theme raised is about life, this theme is supported by the setting which tells the place and time of events from grandparent's arrival until grandpa hands over the savings he has saved for 20 years. in the future, so that it supports the theme elements and other elements. Apart from the elements of theme, setting and plot, there is another element, namely point of view. The point of view in the lawsuit short story is first person point of view where I am the main character. Apart from having a connection between elements, the short story Eyang also presents the moral values ??that Putu Wijaya wants to convey to readers. The moral message conveyed by Putu Wijaya in the short story Eyang is, to be honest in doing things, not to insult other people, and to be trustworthy in your work. The moral messages conveyed often produce different interpretations from each reader, but Putu Wijaya in writing his short stories is able to make readers appreciate the meaning.